Pengaruh Karakteristik Wirausaha, Modal Usaha, dan Penggunaan Informasi Akuntansi Terhadap Keberhasilan Usaha (Studi pada UMKM Desa Banyuurip Kecamatan Ujungpangkah Kabupaten Gresik) - Sabikhin, Miftakhul; Amin, Moh.; Hidayati, Irma (Universitas Islam Malang, 2024)
The most important thing that entrepreneurs want to achieve is business success. This research aims to determine the influence of Entrepreneurial Characteristics, Business Capital, and Use of Accounting Information on MSMEs in Banyuurip Village, Ujungpangkah Subdistrict, Gresik City. The data collection technique used in this research was distributing questionnaires. The data analysis method used is quantitative with Descriptive Statistics analysis, Instrument Test (Validity Test and Reliability Test), Classic Assumption Test (Normality Test, Multicollinearity Test, and Heteroscedasticity Test), and Hypothesis Test (F Test and t Test). The results of this research state that Entrepreneurial Characteristics, Business Capital, and Use of Accounting Information have a positive effect, both partially and jointly, on the success of MSMEs in Banyuurip village, Ujungpangkah subdistrict, Gresik City.Keywords: Entrepreneurial characteristics, business capital, use of accounting information, success of MSMEs